Structural alterations, asymmetry and response inhibition in obsessive-compulsive disorder - Teo, Jia Li (2019)
Obsessive-compulsive disorder (OCD) is a chronically debilitating disorder, with a marginally higher lifetime prevalence rate in Singapore. Earlier studies have been partly inconsistent in the structural basis of OCD. Most of these studies employed a voxel-based morphometry approach and evaluated only volumetric alterations. Few studies have examined more specific sub-components, such as cortical thickness and area, which are phenotypically and genetically independent. Response inhibition, a candidate endophenotype in OCD, has often been emphasized as right-lateralized in imaging studies. While alterations in structural asymmetry have been widely studied and linked to cognitive and emotional disturbances in neuropsychiatric disorders, no studies have examined the link between structural asymmetry and response inhibition in OCD. Therefore, the present study investigated structural alterations in OCD using surface-based morphometry and examined for alterations in structural asymmetry associated with response inhibition and the pathology of OCD. T1-weighted structural magnetic resonance images were acquired from 19 patients with OCD and 21 controls. A whole-brain analysis was conducted using FreeSurfer v6.0 to examine for alterations in cortical thickness, area and volume in patients with OCD. Group differences in asymmetry indices of selected apriori response inhibition and cortico-striato-thalamo-cortical (CSTC) regions were also examined. Compared to controls, patients with OCD showed decreased area and volume in left superior-inferior parietal and occipital regions and increased volume in right supramarginal and postcentral regions. Patients with OCD also exhibited significant leftward asymmetries in several frontal regions, not observed in healthy controls. The present findings highlighted the importance of studying regions beyond the CSTC disease model and suggested potential structural asymmetry underlying inhibitory deficits, thereby prompting further investigation of the underlying mechanisms.